ECCO Essential Requirements for Quality Cancer Care: Soft Tissue Sarcoma in Adults and Bone Sarcoma. A critical review. (February 2017) - Andritsch, Elisabeth; Beishon, Marc; Bielack, Stefan; Bonvalot, Sylvie; Casali, Paolo; Crul, Mirjam; Delgado-Bolton, Roberto; Donati, Davide Maria; Douis, Hassan; Haas, Rick; Hogendoorn, Pancras; Kozhaeva, Olga; et al.
Highlights: ECCO essential requirements for quality cancer care are position papers on delivering high-quality care. Each paper focuses on a tumour type, in this care soft tissue (adult) and bone sarcoma. Sarcomas are rare, and a challenging group of cancers to treat. High-quality care can only be a carried out in specialised sarcoma units or centres. The essential, multidisciplinary details for such units are set out by an expert group. Abstract: Background: ECCO essential requirements for quality cancer care (ERQCC) are checklists and explanations of organisation and actions that are necessary to give high-quality care to patients who have a specific tumour type. They are written by European experts representing all disciplines involved in cancer care. ERQCC papers give oncology teams, patients, policymakers and managers an overview of the elements needed in any healthcare system to provide high quality of care throughout the patient journey. References are made to clinical guidelines and other resources where appropriate, and the focus is on care in Europe. Sarcoma: essential requirements for quality care Sarcomas – which can be classified into soft tissue and bone sarcomas – are rare, but all rare cancers make up more than 20% of cancers in Europe, and there are substantial inequalities in access to high-quality care. Sarcomas, of which there are many subtypes, comprise a particularly complex and demanding challenge for healthcare systems and providers. This paper presents essential requirements for quality cancer care of soft tissue sarcomas in adults and bone sarcomas. High-quality care must only be carried out in specialised sarcoma centres (including paediatric cancer centres) which have both a core multidisciplinary team and an extended team of allied professionals, and which are subject to quality and audit procedures. Access to such units is far from universal in all European countries. It is essential that, to meet European aspirations for high-quality comprehensive cancer control, healthcare organisations implement the requirements in this paper, paying particular attention to multidisciplinarity and patient-centred pathways from diagnosis and follow-up, to treatment, to improve survival and quality of life for patients. Conclusion: Taken together, the information presented in this paper provides a comprehensive description of the essential requirements for establishing a high-quality service for soft tissue sarcomas in adults and bone sarcomas. The ECCO expert group is aware that it is not possible to propose a 'one size fits all' system for all countries, but urges that access to multidisciplinary teams is guaranteed to all patients with sarcoma.